2016
DOI: 10.1139/cjfr-2015-0328
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hemlock woolly adelgid infestation on the physiological and reflectance characteristics of eastern hemlock

Abstract: The hemlock woolly adelgid (HWA) (Adelges tsugae Annand) is an invasive insect in the eastern United States. Since its initial detection in Richmond, Virginia, in 1951, HWA has spread to half of the eastern hemlock (Tsuga canadensis (L.) Carr.) natural range. Detection of early infestation symptoms via remote sensing requires the knowledge of the changes in reflectance resulting from physiological changes in the host as inflicted by the insect and the selection of equipment with the appropriate sensor characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Leaf-level stress and gas exchange were also strongly related to light treatment, albeit counterintuitively, as assimilation rates generally decreased with increasing light and lower levels of infestation. This finding contrasts with other studies that have shown negative gas-exchange responses to HWA infestation and other sap-feeding insects (Zvereva et al, 2010;Gonda-King et al, 2014;Rubino et al 2015) but agrees with studies that have shown possible compensatory increases in photosystem function during the early stages of infestation (Williams et al 2016). In the current study, the negative relationship between light treatment and assimilation may have resulted from a variety of factors including damage to photosystem II from excessive visible light following freezing, lower N concentration in light-exposed leaves, or some combination of factors over the course of the study (Pearce 2001;Larcher 2003).…”
Section: Light Effects On Leaf Physiology and Plant Carbon Balancesupporting
confidence: 71%
“…Leaf-level stress and gas exchange were also strongly related to light treatment, albeit counterintuitively, as assimilation rates generally decreased with increasing light and lower levels of infestation. This finding contrasts with other studies that have shown negative gas-exchange responses to HWA infestation and other sap-feeding insects (Zvereva et al, 2010;Gonda-King et al, 2014;Rubino et al 2015) but agrees with studies that have shown possible compensatory increases in photosystem function during the early stages of infestation (Williams et al 2016). In the current study, the negative relationship between light treatment and assimilation may have resulted from a variety of factors including damage to photosystem II from excessive visible light following freezing, lower N concentration in light-exposed leaves, or some combination of factors over the course of the study (Pearce 2001;Larcher 2003).…”
Section: Light Effects On Leaf Physiology and Plant Carbon Balancesupporting
confidence: 71%
“…Furthermore, it would be meaningful to measure leaf traits in American beech trees that exhibit no symptoms of BLD to determine if there is a difference between asymptomatic leaves within an infected tree comparable within a tree that is void of disease. Many tree species demonstrate a compensatory response to defoliation via an upregulation of photosynthesis (Reich et al, 1993;Williams et al, 2016;McIntire et al, 2020), thus it's feasible that residual leaves within diseased American beech trees attempt to account for a net loss of carbohydrate. The compounding stress induced by multiple years of carbon limitation associated with BLD may become a consequential factor for inciting tree mortality, especially when coupled with other pests, diseases, and environmental elements.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, image data with higher spectral resolution than Landsat's seven bands may have offered an opportunity to evaluate more spectrally distinct absorptive or reflective characteristics of BWA infestation. Once again, BWA-specific hyperspectral studies are limited [32,34], but studies of other insects have demonstrated promise, including the widespread and related hemlock woolly adelgid [90].…”
Section: Discussionmentioning
confidence: 99%